Determinants of Tax Agressiveness in Mining Companies Listed on the IDX - Abimanyu, Anggito; Pangayow, Bill; Seralurin, Yohanes; Bleskadit, Novalia; Salle, Hesty T.; Wonar, Klara (Journal of International Conference Proceedings, 2023)
The objective of this study is to assess the impact of various factors, namely firm size, institutional ownership, capital intensity, profitability, and leverage, on the level of tax aggression exhibited by firms. The study's sample consisted of mining businesses that were listed on the IDX. A purposive sampling technique was employed to choose a total of 20 companies. The study employed purposive sampling as the technique of analysis. The collected data were subjected to statistical analysis using SPSS version 25. This study reveals institusional ownership and profitability exhibit itive impact on tax aggressiveness in this scenario, suggesting that the corporation in displaying an escalating towards tax aggressiveness. In Variables Update, researchers add profitability and leverage to support their research by examining whether these variables have a positive impact on tax aggressiveness. And take a closer look at the impact of mining companies on government revenue.